Household capital structure and financial resilience: evidence from the Netherlands - Ammerman, David Allen (Kansas State University, 2017)
Since 2008, the effects of the Great Recession have lingered in memory and in public discourse, and have underscored the need to better understand the determinants of financial resilience. Financial resilience refers to the household’s ability to absorb and respond to financial shocks (MacKinnon & Derickson, 2013). A financial shock may be induced by a rapid decline in income or asset values, an increase in expenses, or some combination thereof. Solvency -- the relationship between a household’s assets and liabilities -- is one aspect of financial resilience: maintaining a healthy debt ratio affords a household the opportunity to liquidate assets to meet debt obligations in response to a financial shock. Thus, the practical question which inspired this dissertation was "what is the right amount of debt for the household?" Within the personal finance and consumer economics literature, borrowing and saving -- behaviors which influence household solvency -- are conceptualized in part as functions of individual future orientation. The premise that resources are fungible, however, has led to the characterization of concurrent borrowing and saving as a behavioral anomaly. Corporate finance, by contrast, does not characterize this common practice as an anomaly, but suggests that concurrent borrowing and saving is, in part, a matter of balancing the costs and benefits of debt. However, theories of corporate finance cannot predict or explain how individual future orientation might influence a household’s capital structure. Thus, this dissertation adds to the literature by exploring precisely this question: how does individual future orientation influence household capital structure? The present results suggest, in contrast to the existing body of research, that future orientation is positively associated with an individual’s propensity to use leverage to finance investments; but that within a complex family resource management system, this individual propensity is moderated by the relative bargaining power of the other members of the household.
Keywords: Personal financial planning; Household finance; Debt